Facile Synthesis of Zinc Carbonate and Zinc Oxide Nanoparticles and Their Antimicrobial Properties - Karki, Guna B.; Parajuli, Kshama; Adhikari, Subhav; Khatiwada, Shankar P.; Adhikari, Rameshwar (Journal of Nepal Biotechnology Association, 2023)
ZnCO3 nanoparticles (NPs) were prepared by the direct precipitation method using zinc nitrate hexahydrate (Zn(NO3)2.6H2O) and ammonium carbonate ((NH4)2CO3) as precursor materials and polyvinyl alcohol (PVA) as capping agent (R1) whereas ZnO NPs were prepared by thermal decarbonation of the prepared ZnCO3 NPs in the absence (R2) and the presence (R3) of polyvinyl alcohol (PVA) as capping agent. Thus, prepared NPs were subjected to characterization by Fourier transform infrared (FTIR) spectroscopy and phase identification by X-ray diffraction (XRD) study. The effects of the prepared NPs towards different microbial species were also considered. The FTIR spectra of the synthesized ZnCO3 nanoparticles showed characteristic peaks at about 480 cm-1 and 1403 cm-1 correlated to the zinc oxide bond (Zn-O) and carbonate group respectively. Similarly, the FTIR spectra showing a peak at 400 cm-1 suggested the formation of ZnO NPs. Likewise, the XRD pattern of the synthesized NPs confirmed the formation of single-phase crystalline ZnO NPs with FCC lattice structure. Using Scherrer’s equation, the crystallite diameter of the prepared nanoparticles was found to be 9, 21 and 17 nm for R1, R2 and R3 samples respectively. The antimicrobial actions against the different species of bacteria and fungi were also observed and it was found that ZnO NPs prepared by using a capping agent showed a higher zone of inhibition, than that without using the capping agent. Thus, in the present study, ZnCO3 and ZnO NPs were prepared by simple, cost-effective precipitation followed by a decarbonation method and these NPs could be a potential antimicrobial agent.